Political Theology Based in Community: Dorothy Day, the Catholic Worker Movement, and Overcoming Otherness - Tomszak, Marty (Lexington Books, 2023)
In Political Theology Based in Community: Dorothy Day, The Catholic Worker Movement, and Overcoming Otherness, Marty Tomszak sutures together the seemingly disparate realms of radical political theology, communally oriented pedagogy, the Catholic Worker movement, and Catholic Social Teaching to carve a new way of doing ethics in our contemporary sphere. Through an adoption of weak theology and anatheism, brought into the fold by John Caputo and Richard Kearney specifically, and partnering them with the groundbreaking work of Dorothy Day and Peter Maurin in their outpouring of works of mercy, Tomszak highlights the hope present in radical hospitality for our world. This hope is addressed to the distinct publics of the academy, the Church, and wider society as this radical ethic provides distinct answers for a multitude of current crises.